THE BIOCHEMICAL ANALYSIS OF SALIVARY ORGANIC COMPOUNDS TO PATIENTS SUFFERING FROM CARIES DISEASE - Cristina-Angela Ghiorghe; Sorin Andrian; Galina Pancu; Irina Nica; Gianina Iovan (Romanian Society of Oral Rehabilitation, 2017)
The aim of this study was to analyze the various salivary organic compounds in 158 patients who were divided into three groups: 32 in the control group (without general diseases), 108 with general diseases (asthma, diabetes) and 18 with head and neck radiotherapy. The values of the salivary organic compounds were compared with those in the blood, in all groups studied. Materials and methods: The study consisted of the collection of saliva in test tubes which were maintained at a temperature of - 20 ° C. The samples were centrifuged at 10,000 rotations per minute. Laboratory analyzes were performed at an automatic analyzer, observing the protocols specific to each parameter studied. The results obtained from each component salivary considered in the study were statistically analyzed by performing comparisons between groups of patients examined and between the values of these components in the blood vs. saliva. Were obtained lower salivary amylase levels in the group of patients that followed the head and neck radiotherapy (M amylase = 44633.3) compared to the group of patients with general diseases (M amylase = 105,440.0) and control group (M amylase = 114,456.3). In our study we observed a high concentration of urea in the study group (30,9mmol/L) and the radiotherapy, compared to control group (27,31mmol / L). In diabetic patients examined in our study we found high levels of salivary glucose (M glucose = 5.35) than the control group (M glucose = 1.34). Conclusions: The results confirm previous observations showing that, through different general diseases are mainly affected parotid salivary glands, salivary source of key organic compounds (amylase, total protein, glucose). The variations of these chemical compounds in saliva have repercussions on the protective effect of saliva against cariogenic microbial agents and cause finally increase caries risk.